The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1002/chem.201603369
|View full text |Cite
|
Sign up to set email alerts
|

Real‐Time NMR Studies of Oxyamine Ligations of Reducing Carbohydrates under Equilibrium Conditions

Abstract: Ligation reactions at the anomeric center of carbohydrates have gained increasing importance in the field of glycobiology. Oxyamines are frequently used in labeling, immobilization, and bioconjugation of reducing carbohydrates. Herein, we present a systematic investigation of these ligation reactions under aqueous conditions. A series of four unprotected monosaccharides (glucose, N-acetylglucosamine, mannose, and 2-deoxyglucose) and one disaccharide (N,N'-diacetylchitobiose) was reacted with three primary and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
35
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(44 citation statements)
references
References 51 publications
8
35
0
1
Order By: Relevance
“…Concerning the oximation conjugation, the reaction between COS-amf and PDHA was carried out with a large excess of the dioxyamine (10 molar eq./amf unit) in order to promote the coupling reaction with one oxyamine group only. Based on results of Baudendistel et al [20], the pH of the solution was kept constant at pH 5 during the reaction, firstly to solubilize COS-amf in the aqueous solvent, but also to ensure that the amine group of PDHA (pKa 4.2 [21]) is more nucleophilic than amine groups of COS-amf (pKa~6.2-7 [14]) towards the aldehyde group of the amf unit. In this condition of pH, the kinetic study of the reaction by 1 H NMR showed clearly: (i) the formation of the oxime group (CH=NO) characterized by two signals at 7.59 and 7.00 ppm for (E)-and (Z)-oxime protons, respectively [21] (Figure 1a); and (ii) the disappearance of the doublet signal at 5.10 ppm corresponding to the amf aldehyde group in its hydrated form (-CH(OH) 2 , below named gem diol group [16,17]; Figure S4 in Supplementary Materials).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning the oximation conjugation, the reaction between COS-amf and PDHA was carried out with a large excess of the dioxyamine (10 molar eq./amf unit) in order to promote the coupling reaction with one oxyamine group only. Based on results of Baudendistel et al [20], the pH of the solution was kept constant at pH 5 during the reaction, firstly to solubilize COS-amf in the aqueous solvent, but also to ensure that the amine group of PDHA (pKa 4.2 [21]) is more nucleophilic than amine groups of COS-amf (pKa~6.2-7 [14]) towards the aldehyde group of the amf unit. In this condition of pH, the kinetic study of the reaction by 1 H NMR showed clearly: (i) the formation of the oxime group (CH=NO) characterized by two signals at 7.59 and 7.00 ppm for (E)-and (Z)-oxime protons, respectively [21] (Figure 1a); and (ii) the disappearance of the doublet signal at 5.10 ppm corresponding to the amf aldehyde group in its hydrated form (-CH(OH) 2 , below named gem diol group [16,17]; Figure S4 in Supplementary Materials).…”
Section: Resultsmentioning
confidence: 99%
“…Concerning the oximation conjugation, the reaction between COS-amf and PDHA was carried out with a large excess of the dioxyamine (10 molar eq./amf unit) in order to promote the coupling reaction with one oxyamine group only. Based on results of Baudendistel et al [20], the pH of the solution was kept constant at pH 5 during the Thanks to their high nucleophilicity in a large range of pH, oxyamines (pKa~4-5 [18]) have recently been described as a powerful chemo-selective tool for the reducing-end conjugation of various oligosaccharides in the development of new glycoconjugates [19,20]. Thus, dioxyamines conjugated to oligosaccharides could be particularly relevant precursors for the elaboration of advanced oligosaccharides-based materials.…”
Section: Introductionmentioning
confidence: 99%
“…This is, however, at the expense of sacrificing the natural O-glycan core monosaccharide. However, the predicted beta-configuration of the ring-closed form of oxime-linked Gal-NAc similar to GlcNAc would be a disadvantage for lectins and antibodies which recognize the GalNAc core in alpha-configuration [101]. There are several conditions for release of O-glycans under nonreductive conditions as reviewed by Chai and colleagues [100]; however, the yields of core-intact O-glycans (without peeling) are low.…”
Section: Discussionmentioning
confidence: 99%
“…Even though oximes (‐C=N‐O‐) have a long history of being employed in the context of bioconjugation and soft materials, examples of oxime condensation for dynamic covalent self‐assembly are rare. One possible explanation is that the oxime bond is considered too inert to allow for dynamic error‐checking and self‐correcting.…”
Section: Dynamic Covalent Self‐assembly Based On Oxime Formationmentioning
confidence: 99%